The Pursuit of a Combined Educator-Counselor Identity: Gaps and Opportunities in School Counselor Training Scholarship - Ian Levy; Natalie A Edirmanasinghe; Kara Ieva; Sam Steen (Teaching and Supervision in Counseling, 2024)
This special issue focuses exclusively on the training of future school counselors to adopt a non-dual and non-hierarchical identity as an EducatorCounselor. It is long documented that the school counselors’ straddling the worlds of education and counseling have led to identity and role confusion. Concerns about school counselors’ identity have persisted amidst changes in the counseling profession and resulted in a notable schism among leaders and professional associations. Building on the Levy and Lemberger-Truelove (2021) proposition that school counselors are EducatorCounselors, or school-building educators who consistently engage in educational tasks while being oriented by counseling, articles within this special issue offer the field of counselor education an opportunity to understand how shifts in our professional practice, preparation, supervision, and research dissemination can operationalize a clear and distinct EducatorCounselor identity for school-counselors-in-training.
Keywords: Educator-counselor; school counselor education; school counseling